Attitudes towards Research (EACIN-R): Psychometric Evidence of Social Workers in Cartagena de Indias, Colombia - Álvarez-Merlano, Nicolás (Prospectiva. Revista de Trabajo Social e Intervención Social, 2024)
The aim of this article is to report the psychometric properties of the Scale of Attitudes towards Research-Revised version in a Colombian population sample. Two instrumental quantitative studies were conducted using a cross-sectional survey methodology. In the first study, the questionnaire was applied to 141 university students, and in the second to 159 students, all belonging to the Social Work program of a private university institution in Cartagena de Indias. The data were subjected to internal consistency and factor structure analysis through exploratory factor analysis (AFE) and confirmatory factor analysis (AFC). The results of the AFE allowed reducing the scale maintaining three dimensions, which were tested by the AFC. The final version of the instrument consisted of 27 items and three dimensions. The model was deemed appropriate according to the goodness-of-fit indices and the reliability coefficients obtained for each subscale and the total scale. This instrument is a reliable and valid tool for assessing the predisposition to research in university students of Social Work in the city.